EVOLUTION OF PROJECT MANAGEMENT METHODS: WORLD EXPERIENCE AND DEVELOPMENT FEATURES (European Journal of Economics, Finance and Business Development, 2025)
In the fast-growing field of international project management, automated systems and artificial intelligence (AI) are becoming integral components that enhance efficiency, decision-making, and collaboration between diverse teams. This article explores various ways to integrate automated systems and AI into project management processes, highlighting their potential to optimize resource allocation, streamline workflows, and improve communication. The article examines case studies and current trends to highlight the transformative impact of these technologies on project planning, implementation and monitoring in international contexts. In addition, it discusses the challenges and considerations of implementing such innovative approaches, emphasizing the importance of organizational adaptation. Ultimately, this research provides insight into how automated systems and artificial intelligence can drive project success in a global marketplace characterized by complexity and constant change.